Observasi Klinik Pemberian Jus Buah Naga Merah (Hylocereus polyrhizus) dan Jambu Biji (Psidium guajava) Terhadap Peningkatan Kadar Hemoglobin Wanita Menstruasi - Suci Aprisilia Kartika; Risna Agustina; Islamudin Ahmad (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2020)
Anemia is a condition when the blood hemoglobin level is less than normal because to iron deficiency. Red dragon fruit (Hylocereus polyrhizus) and guava (Psidium guajava) are sources of iron which can increase blood hemoglobin levels. The purpose of this study to determine the effect of dragon fruit juice and guava juice on increasing blood hemoglobin levels for menstruating women. The design of this research was Quasy Experimental Pre-Post Design which was conducted in two test groups. The first grup was given dragon fruit juice and the second group was given guava juice. Sampling was determined by purposive sampling based on inclusion and exclusion criteria. The hemoglobine level was using the Easy Touch GCHB tool and analyzed by the Paired Sample T-Test. The results showed that the effect of dragon fruit and guava juice on the hemoglobin level of menstruating women before the intervention in first group test was 11.5 g / dl, second group test was 10.5 g / dl and after the intervention the average was 13.6 g / dl and 13.5 g / dl. Based on the results of the Paired Sample T-Test statistical analysis which has a p value